2024
DOI: 10.1097/ccm.0000000000006176
|View full text |Cite
|
Sign up to set email alerts
|

Position Paper on the Reporting of Norepinephrine Formulations in Critical Care from the Society of Critical Care Medicine and European Society of Intensive Care Medicine Joint Task Force

Patrick M. Wieruszewski,
Marc Leone,
Benjamin Skov Kaas-Hansen
et al.

Abstract: Objectives: To provide guidance on the reporting of norepinephrine formulation labeling, reporting in publications, and use in clinical practice. Design: Review and task force position statements with necessary guidance. Setting: A series of group conference calls were conducted from August 2023 to October 2023, along with a review of the available evidence and scope of the problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Given these potentially dangerous clinical implications, we agree with Wieruszewski et al that there is no reason to delay the prospective implementation of a standardized reporting to norepinephrine base [6], especially with the forthcoming results of large multinational randomized controlled studies on septic shock [7].…”
supporting
confidence: 76%
“…Given these potentially dangerous clinical implications, we agree with Wieruszewski et al that there is no reason to delay the prospective implementation of a standardized reporting to norepinephrine base [6], especially with the forthcoming results of large multinational randomized controlled studies on septic shock [7].…”
supporting
confidence: 76%
“…Recent data have highlighted the relative safety of short term (< 48 h), low dose (< 15 mcg/min) administration of norepinephrine diluted at 64 mcg/mL through peripheral intravenous access [ 9 ], notwithstanding, administration through central venous access is still hegemonic and advisable in current ICU practice. There is significant worldwide variability on drug formulations, as norepinephrine can be found either as tartrate, bitartrate or hydrochloride salts, with different molecular weights and potency equivalence to norepinephrine base, being tartrate the weakest formulation [ 10 ]. Similarly, there is heterogeneity of practice on how to titrate the drug infusion, either using absolute (i.e., mcg/min) or weighted values (i.e., mcg/kg/min).…”
Section: Current Dosing Strategiesmentioning
confidence: 99%
“…However, this heterogeneity could impact the interpretation and exchangeability of clinical data, design and execution of research, and compliance with expert’s recommendations. Thus, homogenization and consensus should be sought [ 10 , 11 ].…”
Section: Current Dosing Strategiesmentioning
confidence: 99%
“…Several salt formulations of NE (tartrate, bitartrate, or hydrochloride) are available in worldwide markets, with the preparation used varying between and even within countries [ 9 ]. Each salt has unique conversion rates to norepinephrine base, the drug's active molecule [ 10 , 11 ]. A recent expert consensus raised awareness of the heterogeneity of NE dose reporting, as clinicians and researchers often fail to specify whether the administered doses are reported as salt or as its base molecule equivalent [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each salt has unique conversion rates to norepinephrine base, the drug's active molecule [ 10 , 11 ]. A recent expert consensus raised awareness of the heterogeneity of NE dose reporting, as clinicians and researchers often fail to specify whether the administered doses are reported as salt or as its base molecule equivalent [ 10 ]. In fact, two large surveys showed that around 50% of respondents are unaware of on which formulation is NE reported locally and, therefore, administered in their practice [ 12 ], leading to potential guideline interpretation disagreements between practitioners [ 13 ].…”
Section: Introductionmentioning
confidence: 99%